2004
DOI: 10.1099/mic.0.27303-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate reduction and the nitrogen cycle in archaea

Abstract: The nitrogen cycle (N-cycle) in the biosphere, mainly driven by prokaryotes, involves different reductive or oxidative reactions used either for assimilatory purposes or in respiratory processes for energy conservation. As the N-cycle has important agricultural and environmental implications, bacterial nitrogen metabolism has become a major research topic in recent years. Archaea are able to perform different reductive pathways of the N-cycle, including both assimilatory processes, such as nitrate assimilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
177
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(189 citation statements)
references
References 148 publications
4
177
0
8
Order By: Relevance
“…But further research is required to substantiate this assumption as only limited information is available for archaeal denitrification in soil ecosystems so far (for example, Bartossek et al, 2010;Hayatsu et al, 2008). However, it has been confirmed that several archaeal members perform both assimilatory and dissimilatory reduction processes to produce for example, N 2 O (Hayatsu et al, 2008;Cabello et al, 2004;Zehr and Ward, 2002), and their actual contribution to denitrification was proven by the presence of denitrification genes (for example, nir and nos genes) in the genomes of several archaeal species (Bartossek et al, 2010;Cabello et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But further research is required to substantiate this assumption as only limited information is available for archaeal denitrification in soil ecosystems so far (for example, Bartossek et al, 2010;Hayatsu et al, 2008). However, it has been confirmed that several archaeal members perform both assimilatory and dissimilatory reduction processes to produce for example, N 2 O (Hayatsu et al, 2008;Cabello et al, 2004;Zehr and Ward, 2002), and their actual contribution to denitrification was proven by the presence of denitrification genes (for example, nir and nos genes) in the genomes of several archaeal species (Bartossek et al, 2010;Cabello et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Soil N cycling includes both reductive and oxidative processes, in which soil microbes have a predominant role (Cabello et al, 2004). Key microbial processes within the soil N cycle are catalyzed by key enzymes, including amoA gene encoding a subunit of ammonia monooxygenase in nitrification, as well as nirS and nirK gene (nitrite reductases) and nosZ gene (nitrous oxide (N 2 O) reductase) involved in denitrification.…”
Section: Introductionmentioning
confidence: 99%
“…Denitrifying organisms include various bacteria, some archaea, and even eukaryotes (Cabello, Roldán & Moreno-Vivián, 2004). Only a few cultured archaea are capable of denitrification; Haloferax genus plays an important role in that sense grouping several species able to perform partial or even complete denitrification as mentioned before (Hfx.…”
Section: Denitrificationmentioning
confidence: 99%
“…As archaea participate extensively in the cycling of nitrogen and sulfur (Canfield and Raiswell, 1999;Cabello et al, 2004), and previous 16S rRNA detection of the Thorarchaoeta in anaerobic aquatic sediments is broadly consistent with these geochemical roles, we searched the Thorachaeota genomic bins for the presence of relevant genes. All three of these archaeal bins have homologs to sulfohydrogenase, which has been shown to be involved in the reduction of elemental sulfur in the archaeon P. furiosus (Ma et al, 1993).…”
Section: The Possible Role Of Thorarchaeota In Sulfur Cyclingmentioning
confidence: 99%